PENGEMBANGAN ALAT PERAGA MATEMATIKA PERKALIAN BAMBU SELIP UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN SISWA KELAS 3 SD - Leonardus Nardi; Suhandi Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research uses Research and Development (R&D) research. This product development refers to the theory of Borg and Gall (1988) including ten stages (Sukmadinata, 2017: 169-170): research and data collection, planning, developing an initial product draft, conducting initial field trials, revising trial results, field testing main product, product revision, wide-scale field trials, final product revision, dissemination and implementation. Research subjects in class III of Kanisius Cungkup Elementary School, Salatiga. The design used for preparing media is the ASSURE model (analyze, state, select, utilize, require, and evaluate). Data was obtained through interview and observation instruments. Data analysis was carried out using descriptive percentage analysis. The research results of the media product "Multiplication Bamboo Selip" were validated by 3 experts, namely learning design experts with a percentage score of 89% with reference to the category ≥ 61% so that it can be categorized as "Very High" (Valid), material experts with a percentage score of 78% with reference to category ≥ 61% so it can be categorized as "High" (Valid) and media experts with a percentage score of 80% with reference to the media category ≥ 61% so it can be categorized as "High" (Valid). The effectiveness of the Bamboo Slip Multiplication mathematics teaching aid based on the results of the difference test or T-test obtained a sig. (2-tailed) value of 0.002 < 0.05, so there is a difference between the experimental class and the control class with the average post-test assessment of students who used it. props, namely 81.38. Meanwhile, the average post-test score for students who did not use teaching aids was 69.31.”